EMBODIED EXPERIENCE IN NOVELS WRITTEN BY INDONESIAN BLIND AUTHORS: A PHENOMENOLOGICAL STUDY OF PERCEPTION - I Made Astika; Faruk; Pujiharto (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe how embodied experience is presented in novels written by blind Indonesian authors. The scope of the study is focused on the embodied experiences of blind characters in the novels Mata Kedua (2013) and Dunia Tanpa Cahaya (2015) by Ramaditya Adikara, as well as the novel Nafas Sang Pekat (2014) by Nabiel Ghali Azumi. The research employs a qualitative approach using a phenomenological textual analysis method. The analysis is grounded in Maurice Merleau-Ponty’s concepts of the lived body, perception, and being-in-the-world. The data consist of narratives, dialogues, and monologues that represent the bodily experiences of blind characters as they interact with the world, space, and themselves. The findings reveal that embodied experience in these novels is articulated through three main forms: the presence of the world in multisensory perception, spatial orientation through the body, and self-understanding within embodied experience. The findings demonstrate that their world remains present and meaningful through sounds, aromas, touch, and other sensory experiences. Furthermore, the body functions as a center of orientation that enables the subject to inhabit space and establish relations with the environment. Blindness is depicted as a different way of perceiving, living, and making sense of reality. These findings offer an alternative perspective to ableist views that tend to define human ability solely on the basis of visual capacity.